2016
DOI: 10.1038/onc.2016.25
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding antisense RNA KRT7-AS is activated in gastric cancers and supports cancer cell progression by increasing KRT7 expression

Abstract: Alterations in long non-coding RNAs (lncRNAs) are associated with human carcinogenesis. One group of lncRNAs, which are antisense in orientation to coding mRNAs (ASs), have been recently described in cancers but are poorly understood. We sought to identify ASs involved in human gastric cancer (GC) and to elucidate their mechanisms of action in carcinogenesis. We performed massively parallel RNA sequencing in GCs and matched normal tissues, as well as in GC-derived and normal gastric epithelial cell lines. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 44 publications
10
102
0
Order By: Relevance
“…Our findings provide important insights into CRC pathogenesis, and are expected to facilitate the development of approaches for early diagnosis and targeted therapy of CRC based on lncRNAs. Recent investigations have revealed that antisense transcripts can exert effects via inducing their neighbouring protein-coding genes [60-62]. However, whether SH3PXD2A-AS1 can modulate SH3PXD2A and other possible target genes is still unclear, and the underlying mechanisms have not yet been explored in this study.…”
Section: Discussionmentioning
confidence: 77%
“…Our findings provide important insights into CRC pathogenesis, and are expected to facilitate the development of approaches for early diagnosis and targeted therapy of CRC based on lncRNAs. Recent investigations have revealed that antisense transcripts can exert effects via inducing their neighbouring protein-coding genes [60-62]. However, whether SH3PXD2A-AS1 can modulate SH3PXD2A and other possible target genes is still unclear, and the underlying mechanisms have not yet been explored in this study.…”
Section: Discussionmentioning
confidence: 77%
“…Knockdown of CASC9 in ESCC cells reduced their migration and invasion. In an investigation of gastric adenocarcinomas, levels of lncRNA KRT7-AS were significantly higher in tumors than in matched normal adjacent gastric tissues 51 . This lncRNA contains regions that are antisense to the protein-coding keratin 7 gene ( KRT7 ); surprisingly, RNA hybrids formed between these transcripts increase expression of KRT7 mRNA and protein.…”
Section: Lncrnas In Be and Eacmentioning
confidence: 95%
“…Specifically, yeast work revealed that caloric restriction activates the R-loop suppressing proteins Rnh1/201 (yeast RNaseH1/2) and Pif1 (ATP-dependent RNA helicase) [15,45]. RNaseH enzymes can degrade the RNA component of RNA-DNA hybrids within R-loops [46,47].…”
Section: Wide-ranging Molecular Functions Of Ataxin-2mentioning
confidence: 99%